Zero-energy infill housing: front and back house options in Manhattan Kansas - Pradhan, Trishna Rani (Kansas State University, 2008)
This thesis was undertaken to investigate and seek possible architectural solutions to two issues. Firstly, fragmentation of the American family structure into a variety of new household types presents new design challenges to architects today. The single family house, once an 'ideal family' home, now needs to be redesigned to accommodate these changing lifestyles. Secondly, global warming and threats of an impending energy crisis loom large over humankind today. Environmentally-responsive architectural design can and should address both of these burgeoning problems. A program was developed as the basis for designing new infill housing in the city of Manhattan, Kansas, a small Midwestern college town. The aim was to provide dwelling units that would accommodate a wide range of family types and use patterns of the entire life cycle while fitting in to the existing architectural fabric of the neighborhood. After a literature review, it was concluded that 'front and back house' design was the most suitable option. In this context, three types of front and back house designs are presented. These options are further divided into thirteen subtypes. It is shown that these designs fulfill the spatial needs of a variety of differing households such as houses with an office, a multigenerational home and units that permit aging in place. An independent study was undertaken to achieve a 'zero energy threshold' for one of the designs within the design matrix presented in the thesis. A 60%-65% decrease in energy usage was attained in the front house and 50% in the back house by increasing the overall efficiency of the building envelope and by utilizing energy efficient appliances. Utilization of a 2 X 6.4 kW grid-connected solar photovoltaic system provided enough energy to power the house (inclusive of front & back houses). A Geothermal heating/cooling system was employed to further decrease the use of fossil fuel. With reduced energy needs and use of a gird connected solar system it was possible to achieve a 'net-zero energy house', which is defined as a house that generates as much as or more than the total energy it uses over the course of a year. An economic analysis of the front and back house and proposed energy systems was also performed. Calculations suggest that rent from the back house could provide substantial financial benefits to the owner of the front house. Although use of non-conventional energy systems demanded a larger initial investment, studies showed that savings made on the utility bills would eventually help recover this investment within the lifetime of the systems.
Keywords: American family structure; Global warming & energy crisis; Net-Zero Energy House; Front and back housing; Architecture (0729)